Psychological predictors of risky driving: the role of age, gender, personality traits (Zuckerman’s and Gray’s models), and decision-making styles - Aluja, Anton; Balada, Ferran; García, Oscar; García, Luis F. (Frontiers in Psychology, 2023)
The present study was planned to study the relationships between age, personality (according to Zuckerman's and Gray’s psychobiological models) and decision-making styles in relation to risky driving behaviors. The participants were habitual drivers, 538 (54.3%) men and 453 (45.7%) women, with a mean age around 45 years and mainly of middle socioeconomic status. The results indicate that the youngest men and women reported more Lapses, Ordinary violations, and Aggressive violations than the oldest men and women. Women reported more Lapses (d = -.40), and men more Ordinary (d = .33) and Aggressive violations (d = .28) when driving. Linear and non-linear analysis clearly support the role of both personality traits and decision-making styles in risky driving behaviors. Aggressiveness, Sensitivity to Reward, Sensation Seeking played the main role from personality traits, and Spontaneous and Rational decision-making style also accounted for some variance regarding risky driving behaviors. This pattern was broadly replicated in both genders. The discussion section analyses congruencies with previous literature and makes recommendations on the grounds of observed results.